Ebaṃ Rebatī - Mahānti, Asita; Mahānti, Asita (Phreṇḍs Pabliśarsa, 2008)
Collection of stories on the theme of Rebatī, a celebrated story written by Fakir Mohan Senapati, 1843-1918, father of Oriya literature